Reduction in Acute Limb Ischemia With Rivaroxaban Versus Placebo in Peripheral Artery Disease After Lower Extremity Revascularization: Insights From VOYAGER PAD. Issue 23 (7th December 2021) - Hess, Connie N.; Debus, E. Sebastian; Nehler, Mark R.; Anand, Sonia S.; Patel, Manesh R.; Szarek, Michael; Capell, Warren H.; Hsia, Judith; Beckman, Joshua A.; Brodmann, Marianne; Diaz, Rafael; Habertheuer, Peter; et al.
Abstract : Background: Patients with peripheral artery disease (PAD) are at heightened risk of acute limb ischemia (ALI), a thrombotic event associated with amputation, disability, and mortality. Previous lower extremity revascularization (LER) is associated with increased ALI risk in chronic PAD. However, the pattern of risk, clinical correlates, and outcomes after ALI early after LER are not well-studied, and effective therapies to reduce ALI post-LER are lacking. Methods: The VOYAGER PAD trial (Vascular Outcomes Study of ASA [Acetylsalicylic Acid] Along With Rivaroxaban in Endovascular or Surgical Limb Revascularization for PAD; rNCT02504216) randomized patients with PAD undergoing LER to rivaroxaban 2.5 mg twice daily or placebo on a background of low-dose aspirin. The primary outcome was a composite of ALI, major amputation of vascular cause, myocardial infarction, ischemic stroke, or cardiovascular death. ALI was prospectively ascertained and adjudicated by a blinded committee. The cumulative incidence of ALI was calculated using Kaplan-Meier estimates, and Cox proportional hazards models were used to generate hazard ratios and associated CIs. Analyses were performed as intention-to-treat. Results: Among 6564 patients followed for a median of 2.3 years, 382 (5.8%) had a total of 508 ALI events. In placebo patients, the 3-year cumulative incidence of ALI was 7.8%. After multivariable modeling, previous LER, baseline ankle-brachial index <0.50, surgical LER, and longer target lesion length were associated with increased risk of ALI. Incident ALI was associated with subsequent all-cause mortality (hazard ratio [HR], 2.59 [95% CI, 1.98–3.39]) and major amputation (HR, 24.87 [95% CI, 18.68–33.12]). Rivaroxaban reduced ALI relative to placebo by 33% (absolute risk reduction, 2.6% at 3 years; HR, 0.67 [95% CI, 0.55–0.82]; P =0.0001), with benefit starting early (HR, 0.45 [95% CI, 0.24–0.85]; P =0.0068 at 30 days). Benefit was present for severe ALI (associated with death, amputation, or prolonged hospitalization and intensive care unit stay, HR, 0.58 [95% CI, 0.40–0.83]; P =0.003) and regardless of LER type (surgical versus endovascular revascularization, P interaction=0.42) or clopidogrel use ( P interaction=0.59). Conclusions: After LER for symptomatic PAD, ALI is frequent, particularly early after LER, and is associated with poor prognosis. Low-dose rivaroxaban plus aspirin reduces ALI after LER, including ALI events associated with the most severe outcomes. The benefit of rivaroxaban for ALI appears early, continues over time, and is consistent regardless of revascularization approach or clopidogrel use. Abstract : Supplemental Digital Content is available in the text.